STRENGTHENING PANCASILA STUDENT PROFILE IN SCHOOLS IN PERENIALISM VIEW - Luh De, Liska; Suastra, I Wayan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
The Pancasila student profile is a number of characters and competencies that are expected to be possessed by students, which are based on the noble values of Pancasila. The perennialism approach is a method of instilling strong and lasting human good values to students, so that they can understand and believe in noble lives and are able to implement them in everyday life. Perennialism arises because the world situation is full of chaos, poor human behaviour, and disorder, especially moral, intellectual and sociocultural decline. The method used in writing this scientific paper is a qualitative descriptive type that studies existing problems and applicable work procedures. The Pancasila Student Profile has 6 dimensions which include: having faith, fearing of God Almighty, and having a noble character; global diversity; self-sufficient; work together; critical reasoning; and creative. This discussion can be related to the view of perennialism which emphasizes the sustainability of eternal and universal values, as well as character building through a conducive learning environment. In the view of perennialism, strengthening the Pancasila student profile can be done through teaching that emphasizes a deep understanding of Pancasila values as eternal truths that must be mastered by every student.